Developing a Non-Cognitive Diagnostic Assessment Model Based on Social-Emotional Learning through Differentiated Instruction in Social Studies Education - Anindya Fajarini; Abdurrahman Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Non-cognitive assessment in Social Studies (IPS) learning at junior high school level still tends to be general in nature, separated from the learning process, and not yet capable of diagnostic mapping students’ social-emotional needs to support responsive learning for learners’ diversity. On the other hand, although the Social-Emotional Learning (SEL) approach has been widely studied, the development of non-cognitive assessment instruments that are systematically integrated with Differentiated Instruction (DI) principles in the context of IPS learning remains very limited. This gap indicates the need for an assessment instrument that not only measures social-emotional aspects but also functions as a basis for designing differentiated learning. This study aims to develop a diagnostic non-cognitive assessment instrument based on the integration of SEL and DI to support the strengthening of self-awareness, self-management, and social awareness of junior high school students in social studies learning. The method used was research and development (RD) with a modified Borg Gall model. The research instrument includes expert validation questionnaires, individual trials with teachers and students, response questionnaires, and semi-structured interview guidelines. Quantitative and qualitative data were analyzed using descriptive statistics based on percentage. The results showed that the instrument met the validity criteria, with average expert validation scores of 80% for content, 76.7% for psychology, and 93.3% for language, as well as 90% in individual trials. In addition, positive responses were obtained from teachers (89%) and students (87.6%). This instrument is valid, easy to use, contextual, and effective in facilitating the expression of students’ social-emotional needs in social studies learning.